Signal-to-Noise Ratio Enhanced Spectral Domain Optical Coherence Tomography with Dual-balanced Detection. (2016) - Bo, En; Liu, Xinyu; Liu, Linbo
Abstract: Spectral domain optical coherence tomography (SD-OCT) with dual-balanced detection (DBD) for signal-to-noise ratio (SNR) enhancement is developed. The dual-balanced detection in the SD-OCT system inherently achieves two-fold increase of the interested signal amplitude, minimizes the common background noise and suppresses artifacts by combining two phase-opposed interferometric spectra obtained simultaneously in comparison to unbalanced detection configuration, resulting in a significant SNR increase and dc elimination performance. Two interferometric spectrum were captured using a dual-line CCD through the same spectrometer optics. This new design is of lower cost compared with the dual CCD design. The feasibility and validity of this SD-OCT system with dual-balanced detection are demonstrated by experimental measurement of a 95% reflector.